Constructing Solidarity and Social Resilience through Traditional Sisemba Sports in South Sulawesi, Indonesia - Muh. Adnan Hudain; Alimin Alwi; Ahmad Adil (JSW (Jurnal Sosiologi Walisongo), 2025)
Lack of interest in playing traditional sports due to the development of modern games. However, there are areas that still preserve and even foster solidarity and social resilience through traditional sports. This research aims to reveal the process and social value of traditional Sisemba sports in South Sulawesi. The unit of analysis is informed by a sociological perspective, employing a qualitative research method with a descriptive approach. Data collection techniques are direct observation, in-depth interviews, and document analysis. The results showed that traditional Sisemba sports help foster the values of solidarity, cooperation, discipline, and resilience, and serve as an arena for learning the values of cooperation, courage, and loyalty to common rules. The game is often held in traditional rituals, such as harvest thanksgiving and gathering, which makes it more than just a physical activity. The dynamics found in social interaction, sportsmanship, and social ethics, involving both physical and emotional interactions, strengthen solidarity between players and teach the importance of accepting risk as part of life.